The Synthesis of Nanostructured WC-Based Hardmetals Using Mechanical Alloying and Their Direct Consolidation. (13th February 2014) - Al-Aqeeli, N.; Saheb, N.; Laoui, T.; Mohammad, K.
Abstract : Tungsten carbide- (WC-) based hardmetals or cemented carbides represent an important class of materials used in a wide range of industrial applications which primarily include cutting/drilling tools and wear resistant components. The introduction and processing of nanostructured WC-based cemented carbides and their subsequent consolidation to produce dense components have been the subject of several investigations. One of the attractive means of producing this class of materials is by mechanical alloying technique. However, one of the challenging issues in obtaining the right end-product is the possible loss of the nanocrystallite sizes due to the undesirable grain growth during powder sintering step. Many research groups have engaged in multiple projects aiming at exploring the right path of consolidating the nanostructured WC-based powders without substantially loosing the attained nanostructure. The present paper highlights some key issues related to powder synthesis and sintering of WC-based nanostructured materials using mechanical alloying. The path of directly consolidating the powders using nonconventional consolidation techniques will be addressed and some light will be shed on the advantageous use of such techniques. Cobalt-bonded hardmetals will be principally covered in this work along with an additional exposure of the use of other binders in the WC-based hardmetals.